2006
DOI: 10.2320/matertrans.47.1595
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Strength and High Electrical Conductivity Characteristics of Cu-Zr Alloy Wires with Nanoscale Duplex Fibrous Structure

Abstract: The cold drawing of cast Cu 100Àx Zr x (x ¼ 3, 4 and 5 at%) alloys to the reduction ratio of 99.7% was found to cause simultaneous achievement of ultrahigh tensile strength of 1350 to 1800 MPa and high electrical conductivity of 30 to 45%IACS (International Annealed Copper Standard). The cold-drawn Cu 95 Zr 5 alloy wire has a well-developed fibrous structure of fcc-Cu and tetragonal Cu 9 Zr 2 phases. The volume ratio of the fcc-Cu phase was evaluated to be about 76%. A very high density of internal defects was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
(21 reference statements)
1
12
0
Order By: Relevance
“…The lattice parameters obtained from these NBD patterns are shown in Table 2. The table also lists the other lattice parameters calculated at the specific lattice planes of the intermetallic 3 . These results suggested that the intermetallic compounds formed in the eutectic phase changed with the Zr content.…”
Section: Microstructures Of the Wire-drawn Specimensmentioning
confidence: 99%
“…The lattice parameters obtained from these NBD patterns are shown in Table 2. The table also lists the other lattice parameters calculated at the specific lattice planes of the intermetallic 3 . These results suggested that the intermetallic compounds formed in the eutectic phase changed with the Zr content.…”
Section: Microstructures Of the Wire-drawn Specimensmentioning
confidence: 99%
“…In order to improve the strength of copper alloys, composition design and preparation technology have been widely studied [1][2][3][4] . The high strength of copper alloys has been reported to be 900 to 1,500 MPa for Cu-Be base alloys after an optimum age-hardening treatment; 600 to 1,500 MPa for Cu-M (M=Nb or Ag) alloy wires and 1,350 to 1,800 MPa for Cu-Zr alloy wires produced by the heavy cold drawing method [5][6][7][8] . To obtain the high strength performance of copper alloys, complicated subsequent manufacturing processes were needed after casting.…”
mentioning
confidence: 99%
“…1) Recently, Kimura et al have reported that heavily cold worked or cold drawn CuZr alloys with relatively high Zr content from 3 to 5 at% showed the tensile strength of 1350$1800 MPa and electrical conductivity of 30$45% IACS. 2,3) Their results suggested that the Cu-x at% Zr (x ¼ 3$5) alloys had high possibility for application as electrical conductors with high strength. They pointed out that simultaneous occurrence of both high strength and electric conductivity had a close connection with the lamella or fibrous microstructure structures in cold rolled or drawn Cu-Zr alloys.…”
Section: Introductionmentioning
confidence: 94%
“…We have also reported that the cold-rolling was not performed for the Cu-x at% Zr alloys with x > 7 and the strength is highest for x ¼ 5 among the alloys with x ¼ 3, 4 and 5. 2,3) Thus in this work the relationship between the electric conductivity and mechanical strength and the cold-drawning was examined for the Cu-5 at% Zr alloy.…”
Section: Introductionmentioning
confidence: 99%